The Use of Poster Media to Enhance Elementary School Students’ Interest in Literacy - Burhanuddin, Burhanuddin; Mir’atus Sholihah; Baiq Eka Widya Ningsih Hariani Yusrin; Zohratul Aini; Fitri Sonia Ihsani; Rahmatul Hamida (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Posters are one of the most effective instructional media for delivering information visually in an engaging and easily understandable manner for students. This study employed a descriptive literature review approach to analyze the implementation of poster media in the learning process by collecting and reviewing various relevant scholarly articles from educational journals. The findings indicate that poster media are effective in enhancing students’ understanding of learning materials, particularly due to their ability to simplify complex information into more accessible and communicative visual forms. Furthermore, the study reveals that poster media have significant potential to support successful learning outcomes when used appropriately. However, their effectiveness largely depends on the quality of poster design, teachers’ understanding in developing media aligned with learning objectives, and students’ visual characteristics. Therefore, this study contributes important insights that poster media are not only attractive learning aids but also an effective strategy for developing creative and contextual visual education in elementary school settings.